INCREASING STUDENTS WRITING USING SERIES PICTURE AT MA MIFTAHUL ULUM CERMENAN JOMBANG - Khudriyah Khudriyah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
The research aimed to describe how series picture is able to improve the students writing ability of Eleventh students of MA Miftahul Ulum Cermenan Jombang. the researcher conducted action research by four stages: planning, implementing, observing, and reflecting. The subjects of the research were 30 students of the eleventh grade of MA Miftahul Ulum Cermenan Jombang in 2021/2022 academic year. This study was implemented in two cycles. Each cycle consisted of four meetings. The data of the study were gathered through the following instruments: observation checklists, field notes, and test. The data were analyzed to obtain the findings of the research. The findings showed that the appropriate ways used in implementing series picture consisted of the following steps: (1) leading students to the material to be done with familiar and interesting picture, (2) giving examples of essays with interesting series pictures, (3) explanation of writing techniques with interesting series pictures, (4) explanation of the elements of writing simple essays, (5) Making an essay with the interesting and familiar series pictures (6) Repairing the teacher's correction results, (7) Asking students to give questions.